2011
DOI: 10.1177/0961463x11400872
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the experience of ‘remembered’ time: A biopsychosocial exploration

Abstract: Though considerable research has been conducted on the subjective experience of time periods of short duration, little has been written about acceleration of long intervals of remembered time with age. The author reviews and assesses psychosocial, biological, and mathematical considerations contributing toward a comprehensive understanding of why the years seem to 'fly by' increasingly more rapidly. In particular, it is suggested that the powerful impact of social acceleration on our subjective sense of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This also occurs for each component in relation to Cronbach’s alpha value and the element count: Past-Negative, .406, 2; Past-Positive, .396, 2; Future, .483, 2; Present, .580, 3. The impact of a small number of items in the low values of Cronbach’s alpha in ZTPI has also been revealed in other studies (D’Alessio et al., 2003).…”
supporting
confidence: 68%
See 4 more Smart Citations
“…This also occurs for each component in relation to Cronbach’s alpha value and the element count: Past-Negative, .406, 2; Past-Positive, .396, 2; Future, .483, 2; Present, .580, 3. The impact of a small number of items in the low values of Cronbach’s alpha in ZTPI has also been revealed in other studies (D’Alessio et al., 2003).…”
supporting
confidence: 68%
“…The findings in Chile tend to be quite similar to those throughout the world. There is an analogous tendency of groups composed of older respondents toward the Future (Corral et al., 2006; D’Alessio et al., 2003; Díaz Morales, 2006) as is the case in the higher socioeconomic classes (Milfont et al., 2008). However, there are also studies where youth are found to be more future oriented (Liniauskaite and Kairys, 2009) or where there are no significant differences in TPs among individuals related to age or gender (Boniwell et al., 2010).…”
Section: The Ztpi Chile In Comparison With Other Countriesmentioning
confidence: 86%
See 3 more Smart Citations